When 'feminism' becomes a genre: Alias Grace and 'feminist' television. (August 2019) - Cattien, Jana
Alias Grace is just one of the many recent TV shows that was labelled 'feminist' so quickly and with such ease that one is left to wonder how much of a genre 'feminism' has already become. This article interrogates what is at stake for 'feminist' critique in labelling cultural phenomena as 'feminist'. I argue that certain ways of reading Alias Grace as a 'feminist' show preclude an alternative reading in which Alias Grace emerges as a critique of 'feminism' itself. What is at stake in the debate on 'feminism' in popular culture is thus not only whether or not we can recognise the potential for 'feminist' critique that resides within popular culture, but also whether or not we can allow socio-cultural phenomena, like TV shows, to take 'feminism' as an object of critique: to generate the kind of critical movement that renders futile any attempt to stabilise, or reify, the signifier 'feminism' as an ahistorical object with fixed meanings – as a genre even. In so doing, I take it that there is no privileged site from which to engender such movement; and I do not take popular culture as a self-contained domain that could qualify for being such a site. The point, then, is not to treat Alias Grace as a representative case study in popular 'feminism'; but rather, to demonstrate, by way of Alias Grace, the complex and contradictory readings that socio-cultural phenomena are amenable to, and which in turn give rise to critical possibilities that unfold from within these phenomena. Reading Alias Grace critically, as I understand it in this article, means allowing it to be, at one and the same time, a reflection on itself and a reflection on the world in which it so quickly comes to be labelled 'feminist'.